Titanium bioactive surface formation via alkali and heat treatments for rapid osseointegration - De Oliveira, Marcelo Gabriel [UNESP]; Radi, Polyana Alves; Pereira Reis, Danieli Aparecida; Dos Reis, Adriano Gonçalves [UNESP] (FapUNIFESP (SciELO), 2021)
Titanium and its alloys are widely used as implant materials and many studies to accelerate the osseointegration have been performed. This work aims to evaluate the formation of a bioactive surface in commercially pure titanium (cp-Ti) grade 4 after alkali (AT) and heat treatments at 600 °C (AHT600) and 900 °C (AHT900). Characterization techniques were SEM, AFM, Raman, TF-XRD, wettability, nanoindentation and indentation adhesion. Additionally, SBF soaking tests were performed to evaluate apatite growth and showed that alkali and heat treatment accelerates apatite growth. The AT samples formed sodium hydrogen titanate (1 µm thick), and AHT600 and AHT900 formed sodium titanate (1 µm thick), while rutile TiO2 increased with temperature, reaching up to 5 µm thick and the surface changed from slightly hydrophilic to fully hydrophilic. Roughness and surface area increased, especially in AHT900. The hardness of the surface layer was significantly increased by the heat treatment.
Keywords: Alkali-heat treatment; Titanate; Titanium